Trigonometric identities

2009-03-27 1:50 am
1. Prove that
(tanθ sinθ) / (tanθ + sinθ) ≡ (tanθ - sinθ) / (tanθ sinθ)
2. Prove that
(cos2 θ - sin2 θ) / (1 + 2 sinθ cosθ) ≡ (1 - tanθ) / (1 + tanθ)

回答 (2)

2009-03-27 2:21 am
✔ 最佳答案
1. R. H. S.
= (tanθ - sinθ) / (tanθ sinθ)
= {sinθ[(1 - cosθ) / cosθ]} / (sin^2θ/ cosθ)
= (1 - cosθ) / sinθ

L. H. S.
= (tanθ sinθ) / (tanθ + sinθ)
= (sin^2θ/ cosθ) / {sinθ[(1 + cosθ) / cosθ]}
= sinθ/ (1 + cosθ)
= [sinθ/ (1 + cosθ)]*[(1 - cosθ) / (1 - cosθ)]
= [sinθ(1 - cosθ)] / (1 - cos^2θ)
= [sinθ(1 - cosθ)] / sin^2θ
= (1 - cosθ) / sinθ
= R. H. S.


2. R. H. S.
= (1 - tanθ) / (1 + tanθ)
= [(cosθ- sinθ) / cosθ] / [(cosθ+ sinθ) / cosθ]
= (cosθ- sinθ) / (cosθ+ sinθ)
= [(cosθ- sinθ) / (cosθ+ sinθ)]*[(cosθ+ sinθ) / (cosθ+ sinθ)]
= (cos^2θ- sin^2θ) / (cos^2θ+ 2cosθsinθ+ sin^2θ)
= (cos^2θ - sin^2θ) / (1 + 2 sinθcosθ) (Since cos^2θ+ sin^2θ= 1)
= L. H. S.
2009-03-27 9:16 am
1. Prove that(tanθ sinθ) /(tanθ + sinθ) ≡ (tanθ - sinθ) / (tanθ sinθ)
sol
(tanθ +sinθ)(tanθ - sinθ)
=tan^2θ – sin^2θ
=sin^2θ/cos^2θ-sin^2θ
= sin^2θ(1/cos^2θ-1)
= sin^2θ(sec^2θ-1)
= sin^2θtan^2θ
so (tanθ sinθ)/ (tanθ + sinθ) ≡ (tanθ - sinθ) / (tanθ sinθ)
2. Prove that
(cos^2θ – sin^2θ)/ (1 + 2 sinθ cosθ) ≡ (1 - tanθ) / (1 + tanθ)
sol
(1 - tanθ) /(1 + tanθ)
=(cosθ-sinθ)/(cosθ+sinθ)
=(cosθ-sinθ)(cosθ+sinθ)/(cosθ+sinθ)^2

=(cos^2θ – sin^2θ)/(1+2 sinθcosθ)


收錄日期: 2021-04-13 16:32:55
原文連結 [永久失效]:
https://hk.answers.yahoo.com/question/index?qid=20090326000051KK01056

檢視 Wayback Machine 備份